Cell Volume Changes and Membrane Ruptures Induced by Hypotonic Electrolyte and Sugar Solutions - Božič, Bojan; Zemljič Jokhadar, Špela; Kristanc, Luka; Gomišček, Gregor (Frontiers in Physiology, 2020)
The cell volume changes induced by hypotonic electrolyte and sucrose solutions were studied in Chinese-hamster-ovary epithelial cells. The effects in the solutions with osmolarities between 32 and 315 mosM/L and distilled water were analyzed using bright-field and fluorescence confocal microscopy. The changes of the cell volume, accompanied by the detachment of cells, the formation of blebs, and the occurrence of almost spherical vesicle-like cells (“cell-vesicles”), showed significant differences in the long-time responses of the cells in the electrolyte solutions compared with the sucrose-containing solutions. A theoretical model based on different permeabilities of ions and sucrose molecules and on the action of Na+/K+-ATPase pumps is applied. It is consistent with the observed temporal behavior of the cells’ volume and the occurrence of tension-induced membrane ruptures and explains lower long-time responses of the cells in the sucrose solutions.